The relationship between family diet consumption, family environment, parent anxiety and nutrition status children during the COVID-19 pandemic: a longitudinal study - Peng, Lili; Hu, Rui; Feng, Yiwei; Shi, Wei; Zhao, Li; Jiang, Lihua (Frontiers in Public Health, 2023)
The COVID-19 pandemic has exacerbated the trends of childhood overweight, obesity, and malnutrition, as well as increased psychological stress and family conflicts among family members. This study aims to analyze the nutritional status of Chinese children during the COVID-19 pandemic and its relationship with family diet, family environment, and parental anxiety, in order to provide evidence for further interventions in children's nutritional status. This study included 7,645 primary and secondary school students and their parents from five schools in Chengdu, China. Chi-square tests were used to analyze the categorical variables of children's malnutrition, overweight, obesity, and parental anxiety. T-tests were used to assess changes in the continuous variable of family environment between two rounds of follow-up surveys. Multiple logistic regression analysis was employed to examine the impact of changes in family diet during the COVID-19 pandemic on children's nutritional status. Generalized estimating equations were used to analyze the effects of family environment and parental anxiety on childhood obesity. The prevalence of malnutrition and obesity decreased from 11.64%and 11.60% in wave 1 to 4.96% and 10.50% in wave 2, and the rate of overweight increased from 13.11%in wave 1 to 13.73% in wave 2. Children whose families reduced consumption of staple foods during the COVID-19 were more likely to be frail, and families increased consumption of sugary drinks, take-out or meal delivery services, living in towns, family environmental barriers, and parental anxiety were risk factors for overweight obesity. Mother's education level in middle and high school and low age were protective factors for overweight obesity. The physical environment of the family, the emotions of family members, and children's perceptions of the family's soft environment can influence children's eating behaviors, children's nutritional intake, and malnutrition and obesity in children under public health emergencies, and family-based dietary interventions may be effective. Parents can increase consumption of healthy foods and improve the family environment, which improve their growth.